Metal coated and nanofiller doped polycarbonate membrane for hydrogen transport. (22nd November 2018) - Patel, A.K.; Acharya, N.K.
Abstract: The modification in the polymeric membrane combined with metallic film as well as composites with inorganic nanofiller can be used for separation of various gases, with hydrogen gas as it is widely used as fuel material. The change in free volume due to modification in polymer chains alters the transport mechanism. In this work, the transport behaviour of H2 across the different metal coated and nanocomposite membrane has been studied and compared with that of standard polycarbonate membrane. Transport properties changes due to the modification in the composition of nanofiller. A PtPd alloy thin film and iridium thin film of around 8–10 nm was coated on polycarbonate substrate using sputtering technique to make layered polymer nanocomposite membrane. Moreover, SiO2 nanocomposites with 10 wt% and 15 wt % were prepared by solution casting method and the uniform dispersion of silica nanoparticles was obtained by sonication before casting the membrane. Further, the tests were carried at constant upstream pressure 30 psi and at constant temperature 35 °C using constant volume/variable pressure method. Highlights: Improved permeation and separation properties of membrane by metal coating or MMM. The PtPd coating enhances the hydrogen permeability by 17%. Iridium (Ir) coating it drastically changes permeability to 51%. MMM with silica nanofiller by 10 wt% increases the permeability by 27%. MMM increased by 15 wt%, the hydrogen permeation enhances by 66%.